2005
DOI: 10.1055/s-2005-918421
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Substituted Azetidine Type α- and β-Amino Acids

Abstract: A s y m m e t r i c S y n t h e s i s o f S u b s t i t u t e d A z e t i d i n e A m i n o A c i d sAbstract: A versatile asymmetric synthesis of 3-substituted azetidine-2-carboxylic acids and 2-substituted azetidine-3-carboxylic acids via 1,3-amino alcohols with excellent stereoselectivities (de ≥ 96%, ee ≥ 96%) is reported. The high asymmetric inductions were achieved employing the SAMP/RAMP-hydrazone methodology. A phenyl moiety was used as a synthetic equivalent of the carboxylic acid function. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…N -Tosylazetidines 8b are reported compounds in the literature and thus allowed a comparison of the optical rotations ([α] D ( R , R )- trans - 8b +235.6 ( c 0.2, CHCl 3 ) vs +238.5 ( c 1.0, CHCl 3 , ee >99%) in Lit., [α] D ( S , S )- trans - 8b −232.9 ( c 0.3, CHCl 3 ) vs −228.5 ( c 1.0, CHCl 3 , ee = 97%) in Lit. ) confirming the assigned absolute stereochemistry of the N -tosylated 2-arylazetidines 8 and compounds anti - 3 - 6 . Also, the ( R , R )-enantiomer of alcohol ( S , S )- syn - 7b is a known compound in the literature, and thus allowed a comparison of the optical rotations ([α] D ( S , S )- syn - 7b −24.3 ( c 0.4, MeOH) vs ( R , R )- syn - 7b +25.4 and +26.1 ( c 1.0, MeOH) in Lit.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…N -Tosylazetidines 8b are reported compounds in the literature and thus allowed a comparison of the optical rotations ([α] D ( R , R )- trans - 8b +235.6 ( c 0.2, CHCl 3 ) vs +238.5 ( c 1.0, CHCl 3 , ee >99%) in Lit., [α] D ( S , S )- trans - 8b −232.9 ( c 0.3, CHCl 3 ) vs −228.5 ( c 1.0, CHCl 3 , ee = 97%) in Lit. ) confirming the assigned absolute stereochemistry of the N -tosylated 2-arylazetidines 8 and compounds anti - 3 - 6 . Also, the ( R , R )-enantiomer of alcohol ( S , S )- syn - 7b is a known compound in the literature, and thus allowed a comparison of the optical rotations ([α] D ( S , S )- syn - 7b −24.3 ( c 0.4, MeOH) vs ( R , R )- syn - 7b +25.4 and +26.1 ( c 1.0, MeOH) in Lit.…”
supporting
confidence: 72%
“…Reduction of esters 6 with LiAlH 4 in THF for 2.5 h afforded γ-sulfonylamino alcohols 7 in good yields (63−87%) . In a next step these alcohols 7 were cyclized under Mitsunobu conditions to the corresponding N -tosylazetidines 8 in high yields (74−94%) with high enantiomeric excess (>98% ee) …”
mentioning
confidence: 99%
“…Indeed, the N-benzoylaziridine ring can undergo ring opening at either C-2 or C-3 with concomitant expansion. Following this protocol, a-substituted a-hydroxy b-amino acids were obtained in racemic form (Scheme 7.97 Other research groups that have reported aziridine opening in the synthesis of bamino acids are those of Beresford [151], Mordini [152], Davis [153], Enders [154], Yamauchi [155], Wu [156], Matthews [157] and Crousse [158].…”
Section: Synthesis Of B-amino Acids Via Radical Reactionsmentioning
confidence: 99%
“…Azacyclic β-amino acid derivatives are not only potential intermediates for azacyclic bioactive compounds, such as azirinomycin ( 1 ), piperazine surrogate 2 , β-proline ( 3 ), , antipsychotic nemonapride ( 4 ), substance P antagonist CP-99,994 ( 5 ), and croomine ( 6 ), but also interesting building blocks for artificial peptides , (Figure ). We recently reported the asymmetric total synthesis of (−)-kopsinine based on one-pot [ N + 2 + 3] cyclization strategy (Scheme , n = 3), that is, chiral diether-controlled asymmetric conjugate addition of lithium N- benzyltrimethylsilylamide ( 7a : R′ = Me) to indolepropenoate ( 8c : R = N -Boc-indol-3-yl) , followed by C,N-dual alkylation with 1-chloro-3-iodopropane ( 9a : n = 3, X 1 = Cl, X 2 = I). , Herein, we describe an extension of this methodology to realize general entry to enantio- and diastereoselective one-pot [ N + 2 + n ] cyclization for azacyclic β-amino acid derivatives (Scheme , n = 0–4).…”
Section: Introductionmentioning
confidence: 99%